The light inside the shadow an anthology of works by Blue Board members - Allen, Joanne; Anderson, Michelle; Reynolds, Julia (ANU eView, 2013)
"When I first decided to establish BlueBoard I imagined a safe, supportive caring online space where consumers and carers with lived experience of depression could create a community to share their experiences and expertise, understand that they were not alone, and seek help and provide it to others. This would be a place which transcended geographical boundaries and where members could share both the individuality and the universality of their experiences. In this anthology of creative works, BlueBoard members impart these experiences in a form which is accessible to a wider audience."--Foreword